Evidence for a Chromosomally Located Third Integron in Salmonella enterica Serovar Typhimurium DT104b - Daly, M. (American Society for Microbiology, 2004)
Salmonella enterica serovar Typhimurium isolates of phage types DT104 and DT104b are frequently associated with multiple antimicrobial resistance. We describe the characterization of a class 1 integron containing dfrA1 and aadA1, genes from two Salmonella serovar Typhimurium DT104b isolates. Genetic mapping located the integron to the bacterial chromosome in each case.